Effect of culture media, aqueous extracts of the grains and de-oiled cakes on growth of Pleurotus florida - Shendge, K B; Surywanshi, A P (Mushroom Research, 2019)
Effect of various culture media (Ashby’s manitol agar, Yeast extract agar, Czapeck’s dox agar, Yeast manitol agar, Malt extract agar, Potato malt agar, Corn meal agar and Potato dextrose agar), aqueous extracts (each @ 5 and 10%) of cereal and pulse grains (sorghum, wheat, mungbean, maize, pearl millet, pigeonpea, soybean and chickpea) and aqueous extracts of de-oiled cakes (cotton seed cake, neem seed cake, soybean cake, karanj cake, castor cake, sunflower cake, safflower cake and groundnut cake) on mycelia growth of Pleurotus florida was studied in - vitro. Of the culture media tested, Potato dextrose agar exhibited significantly highest mycelial growth (90.00 mm), followed by Czapeck’s dox agar (77.33 mm) and Yeast extract agar (66.67 mm). However, Yeast manitol agar gave significantly least growth (21.90 mm). Of the grains aqueous extracts tested, significantly highest mycelial growth was recorded with sorghum grain extract (79.21 mm), followed by wheat grain extract (77.21 mm), maize grain extract (76.55 mm) and mungbean grain extract (74.70 mm). Of the de-oiled cake aqueous extracts tested, significantly highest mycelial growth was recorded with cotton seed cake (58.01 mm), followed by soybean cake (53.86 mm), castor cake (49.43 mm), sunflower cake (46.24 mm) and groundnut seed cake (46.22 mm). Thus all the culture media, aqueous extracts of cereals / pulses grains and de-oiled cakes were found to encourage the mycelia growth of P. florida. However, Potato dextrose agar and Czapek’s dox agar media; sorghum, wheat and maize grain extracts and cotton, soybean and castor de-oiled cake extracts were found most suitable.